2005
DOI: 10.1680/tran.2005.158.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Development of a vehicle emissions monitoring system

Abstract: Investigation of vehicle emissions with an on-board emissions measurement system can provide a better understanding of how these emissions contribute to air pollution. This paper discusses the design and development by Imperial College London and industrial collaborators of a vehicle performance and emissions monitoring system, including its installation both on test vehicles allowing an interface with the engine management system and those that do not. Results from preliminary field trials and chassis dynamom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Recent research papers have reported on using manufacturers' proprietary software and interface systems in order to communicate with the test vehicles [6,19]. Such experimental arrangements have the advantage of being able to potentially communicate with a given make of vehicle, such as Ford or Renault as in the case of the cited studies.…”
Section: Review Of Driving Cycle Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research papers have reported on using manufacturers' proprietary software and interface systems in order to communicate with the test vehicles [6,19]. Such experimental arrangements have the advantage of being able to potentially communicate with a given make of vehicle, such as Ford or Renault as in the case of the cited studies.…”
Section: Review Of Driving Cycle Developmentmentioning
confidence: 99%
“…Other researchers, using external measurement devices, have focused of vehicle speed and acceleration [16,17]. The ability to connect directly to the ECU has allowed other researchers [6,12,19] to examine certain engine operating characteristics such as engine speed, temperature and throttle position, as well as the parameters mentioned above. Connection to the OBD network of sensors also allows for determination of air-and fuel-flow parameters, in order to better estimate fuel consumption and emissions in near real-time [12].…”
Section: Employingmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations of a conventional vehicle and the two versions of the mechanical hybrid were performed for urban and extra-urban driving cycles, using a computational model of a Ford Focus Estate, developed by Diego-Ayala [22] and North [23]. In this model, steady-state engine maps with correction for engine warm up were used.…”
Section: Simulation Of a Full Size Mechanical Hybrid Vehiclementioning
confidence: 99%